Multi-Cycle Production Development Planning for Sustainable Power Systems to Maximize the Use of Renewable Energy Sources - Wahab Musa; Vadim Ponkratov; Alan Karaev; Nikolay Kuznetsov; Larisa Vatutina; Maria Volkova; Olga Shalina; Andrey Masterov (Civil Engineering Journal, 2022)
This research focuses on the multi-cycle production development planning for sustainable power systems to maximize the usage of renewable energy sources. The intention of this study is to offer a comprehensive review of the research on the potential of multi-cycle production development planning for the development of sustainable power systems. In pursuit of this objective, the study has incorporated a qualitative research approach to analyze the volume of data available on the research topic to delineate how multi-cycle production development planning can be used for sustainable power systems and the maximization of the use of renewable energy sources. The study also highlights the major models that can be incorporated into the multi-cycle production development planning for sustainable power systems to maximize the use of renewable energy sources. The existing literature was extracted from databases, namely, Google Scholar, EBSCOHost, and Springer. The data comprised peer-reviewed journal articles, books, and credible online sources. Lastly, the practical and theoretical relevance of the study, along with limitations and recommendations for future practitioners, is provided in the conclusion. Doi: 10.28991/CEJ-2022-08-11-018 Full Text: PDF